Societal attitudes and structural barriers in coaching para-athletes: A mixed-methods systematic review. - Junyan Liu; Hongjun Yu; Waifong Catherine Cheung; Adam Bleakney; Yih-Kuen Jan (PLoS ONE)
Coaching athletes with disabilities is essential for promoting inclusivity and equity in sports. However, societal attitudes (e.g., stigmatization and ableism) and structural barriers (e.g., insufficient funding and limited access to adaptive equipment) persist as significant obstacles to their full participation and optimal performance. This systematic review addresses a critical gap in the existing literature by examining the complex interaction between societal and structural factors and their impact on coaching practice for athletes with disabilities. A mixed-methods approach was employed to synthesize data from 26 studies sourced from PubMed, Web of Science, SPORTDiscus, and Google Scholar. By integrating both qualitative and quantitative evidence, this review explores how societal biases and resource limitations converge to create systemic challenges that hinder coaching effectiveness. This review indicates that societal perceptions, including ableism and underestimation of athletic potential, in conjunction with structural barriers, such as inadequate facilities and funding, significantly undermine the effectiveness of coaching practices. Moreover, the findings emphasize the urgent need for comprehensive reforms in coach education and policy implementation with a particular focus on improving accessibility and ensuring the equitable distribution of resources. Ultimately, the evidence suggests that addressing these interconnected barriers is essential for fostering a more inclusive and equitable coaching environment for athletes with disabilities.